Design and analysis of a composite drive shaft for an automobile - Muhammad Zulfadhli, Md Zaki (2012)
A hybrid aluminum/composite is an advanced composite material that consists of aluminum tube wound onto outside by layers of composite material. This project investigates the maximum torsion capacity of the hybrid aluminum/composite shaft for different winding angle, number of layers and stacking sequences. The hybrid shaft consists of aluminum tube wound outside of E-glass and carbon fibers/epoxy composite. The finite element method has been used to analyze the hybrid shaft under static torsion. MSC Patran/Nastran finite element software was used to perform the analysis for the hybrid shaft. The shaft model was analyzed. Isotropic properties were used for aluminum tube and orthotropic for composite materials. The results show that the static torque capacity is significantly affected by changing the winding angle, stacking sequences and the number of layers. The maximum static torsion capacity will occur in an aluminum tube wound outside by more layers of carbon fiber/epoxy composite with winding angle of 45.